The Effect of LDR, NPL, and NIM on Profitability in Conventional Commercial Banks on IDX - I Made Kelvin Indra Setiawan; I Made Dana (International Journal of Asian Business and Management, 2024)
Banks are monetary mediators whose work is to gather reserves from the open and convey these reserves to the open. Banks must generate profits from the primary and supporting activities to ensure long-term sustainability and optimize profitability. This study aims to analyze the effect of Loan Deposit Ratio (LDR), Non-Performing Loan (NPL), and Net Interest Margin (NIM) on profitability proxied by the ROA ratio. This research is quantitative in the form of associative. The research population is all conventional commercial banks on the Indonesia Stock Exchange during the observation year 2018-2022, totalling 43 companies. The research sample was obtained from as many as 27 companies based on purposive sampling. The data analysis technique used is panel data multiple linear regression analysis with the help of the EViews 12 program. The results showed that LDR had no significant effect on profitability. NPL has a negative and significant effect on profitability. NIM has a positive and significant effect on profitability